2016
DOI: 10.1099/jgv.0.000529
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of porcine circovirus type 2 from dead minks

Abstract: Circovirus infection is a growing problem in the field of veterinary and public health. It is associated with enteric diseases in both mammalian and avian hosts. In this study, we detected and isolated porcine circovirus strains in the tissue samples of minks that died from diarrhoea in Shandong Province, China. We sequenced the whole genome of two porcine strains of Circovirus, designated as MiSD-1 and MiSD-2, which had a 97.34% similarity on nucleotide sequence and were closely related to porcine circovirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…It is unclear whether PCV3 has been evolving undetected in pigs for some time or whether it originated via cross-species transmission or has arisen via recombination between unidentified parental circoviruses. PCV2 is capable of crossing species barriers, causing fatal disease in species other than swine; a recent report identified PCV2 in six mink that died of diarrhea in China (82).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether PCV3 has been evolving undetected in pigs for some time or whether it originated via cross-species transmission or has arisen via recombination between unidentified parental circoviruses. PCV2 is capable of crossing species barriers, causing fatal disease in species other than swine; a recent report identified PCV2 in six mink that died of diarrhea in China (82).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, cases of infections due to porcine pathogens (such as Hepatitis E virus, Pseudorabies virus) have progressively in minks and foxes (41)(42)(43)(44). PCV2 was also reported in minks, foxes, and raccoon dogs with diarrhea or reproductive failure in China (45)(46)(47). Interestingly, the samples were tested negative for common pathogens (such as Mink enteritis virus, Canine distemper virus, Coronavirus, Rotavirus, or Astrovirus) of minks and foxes, indicating that PCV2 was also an important pathogen contributing to the clinical diseases of minks and foxes.…”
Section: Pcvs In Caninesmentioning
confidence: 99%
“…Possible cross-species transmission of PCV2 is reported in several previous studies [6], [8], [9], [10], [11], [12], [13], [14], which included pig–rodent transmission, pig–mink transmission, pig–human transmission and pig–insect transmission. In this study, we confirmed those buffalo-origin-like PCV2 strains in swine herds in southern China, which further supported the possible cross-species infection of PCV2 between buffalo and pig in this region.…”
mentioning
confidence: 85%
“…However, one animal experimental study demonstrated that calves were susceptible to PCV2 and displayed clinical signs including lymph node swelling, reddening of oral and ocular mucosa and diarrhoea [5]. Moreover, another study suggested that PCV2 might be closely related to the death of minks clinically [6], indicating that PCV2 is also an important pathogen in minks, not just in pigs.…”
mentioning
confidence: 99%